An investigation of e-business risks in UK SMEs. (10th October 2011) - Sukumar, Arun; Edgar, David; Grant, Kevin
Electronic business is a phenomenon that is now well defined and has emerged as a field of study. In parallel, businesses are increasingly embedding technology into their business processes and seeking to exploit the potential efficiency and effectiveness gains that can occur. As such, industry and academic attention has spawned a range of research interests and resulted in proposals of how e-business can be used and exploited. In reviewing a range of academic literature papers, it is interesting to identify a lack of robust, rigours and dependable research into the risks associated with e-business particularly in small to medium size enterprises (SMEs). As such, this paper provides a bridge for the perceived gap in the literature on e-risks, by exploring the perceptions of SMEs towards e-business risk, and seeking to posit a research agenda that will make a meaningful contribution to both academia and industry.